Pharisees, Freudians and the fetishism of the text: Catholic triumphalism in Jacques Lacan. (February 2017) - Burston, Daniel
Abstract: This paper argues that Jacques Lacan (1901–1981) was possibly the most famous Catholic psychoanalyst who was not known for being Catholic. Confusion on this score is understandable, however. He declared himself an atheist at age 16 but in later life, boasted of his Jesuit education, frequently quoted St. Paul, Augustine, and St. Aquinas, and, at the age of 73, pronounced Catholicism to be "the one true religion". Lacan possessed an almost religious veneration for Sigmund Freud, but rejected Freud's theory of psychosexual development and criticised psychoanalysts who invoked Freud's characterology and theories of object relations as "Pharisees". I argue that his bizarre polemics with the International Psychoanalytic Association are the result of habits of thought and feeling he acquired as a child, and then "transferred" from Jesus onto Freud in later life.